Mindful Parenting and Anxiety in Full-time Working Mothers - Nurinayah, Andi; Rinaldi, Martaria Rizky (Jurnal Psikologi Integratif, 2023)
Full-time working mothers face numerous challenges that can lead to anxiety. The aim of this study is to examine the relationship between mindful parenting and anxiety among full-time working mothers. The participants in this study consisted of 99 mothers engaged in full-time employment. The sampling technique used was convenience sampling. Data were collected using the Mindful Parenting Scale and the Anxiety Scale from the Depression, Anxiety, and Stress Scale (DASS). Data were analyzed using product-moment correlation analysis. The results of the data analysis showed a correlation (rxy) = -0.210 with p < 0.050. This result indicates a negative correlation between mindful parenting and anxiety among full-time working mothers, meaning that higher level of mindful parenting is associated with lower level of anxiety. Conversely, lower level of mindful parenting is associated with higher level of anxiety. Therefore, it is recommended to provide intervention to enhance mindful parenting among working mothers to help reduce their anxiety. Ibu yang bekerja penuh waktu mengalami banyak tantangan yang dapat menyebabkan kecemasan. Tujuan dari penelitian ini adalah untuk menguji hubungan antara mindful parenting dengan kecemasan pada ibu yang bekerja penuh waktu.  Partisipan dalam penelitian ini yaitu sejumlah 99 ibu yang menjalani pekerjaan penuh waktu. Teknik sampling yang digunakan yaitu convenience sampling. Data dikumpulkan menggunakan skala mindful parenting dan skala kecemasan dari Depression, Anxiety, and Stres Scale (DASS). Data dianalisis dengan menggunakan analisis korelasi product moment. Hasil analisis data menunjukkan bahwa terdapat korelasi (rxy) = -0,210 dengan p < 0,050. Hasil ini mengindikasikan adanya korelasi negatif antara mindful parenting dan kecemasan pada ibu yang bekerja penuh waktu, artinya semakin tinggi mindful parenting maka semakin rendah kecemasan. Sebaliknya, semakin rendah mindful parenting maka semakin tinggi kecemasan. Dengan demikian, disarankan pemberian intervensi untuk meningkatkan mindful parenting pada ibu bekerja untuk dapat membantu mengurangi kecemasannya.